Game Series: il linguaggio seriale nel mondo videoludico - Barra, Mattia (Mediascapes journal, 2016)
The field of videogames and game studies it’s a quiet recent matter in a research environment, and it’s based on the studying of a medium that’s multifaceted and in continuous evolution. This paper wants to focus on the serialization processes in the videogames industry. At the beginning the concept of “serialization” in videogames referred only to the tie-inworks based on the TV series (Lost: Via Domus, C.S.I., 24) or movie sagas (The Godfather saga, Star Wars), or several sequels of the IP (Intellectual Property) software houses owned, as Super Mario, Assassin’s Creed and so on. Then, at a later time, the continual cross-media and trans-media operations (at first only pointed towards the storytelling) among movies, TV and videogames, generated borderline products. Specifically, it’s possible to find a multitude of video-ludic products released with the television formula of the “season” and “episodes”. This means that if in a first moment a videogame user had a complete story to play, with a beginning and an end, now he has to wait the release of new episodes of the game to continue his play. It’s the case of transmedia spin-off The Walking Dead, Season 1 and Season 2, The Wolf Among Us or the recent Life is Strange which, at present, has just one episode released of five announced. This new type of videogame narration, through the interactive using of the player, considers multiple endings that makes more interesting the development of this serial language.